2018
DOI: 10.1007/s00134-018-5478-0
|View full text |Cite
|
Sign up to set email alerts
|

Early extubation followed by immediate noninvasive ventilation vs. standard extubation in hypoxemic patients: a randomized clinical trial

Abstract: Purpose: Noninvasive ventilation (NIV) may facilitate withdrawal of invasive mechanical ventilation (i-MV) and shorten intensive care unit (ICU) length of stay (LOS) in hypercapnic patients, while data are lacking on hypoxemic patients. We aim to determine whether NIV after early extubation reduces the duration of i-MV and ICU LOS in patients recovering from hypoxemic acute respiratory failure. Methods: Highly selected non-hypercapnic hypoxemic patients were randomly assigned to receive NIV after early or stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 32 publications
2
73
2
3
Order By: Relevance
“…12,16,19,22 Another study confirmed that early extubation followed by immediate NIV application with a full-face mask or helmet can reduce the number of days spent on invasive ventilation without affecting the intensive care unit length of stay in highly selected patients with hypoxaemia. 23 The results of this study show that use of a helmet does not have a significant benefit in terms of the oxygenation index and that compared with standard oxygen therapy or a mask, the helmet does not increase PaCO 2 . As when using the common mask, employing a helmet requires the patient to have effective independent breathing, clear respiratory secretions, and haemodynamic stability.…”
Section: Discussionmentioning
confidence: 65%
“…12,16,19,22 Another study confirmed that early extubation followed by immediate NIV application with a full-face mask or helmet can reduce the number of days spent on invasive ventilation without affecting the intensive care unit length of stay in highly selected patients with hypoxaemia. 23 The results of this study show that use of a helmet does not have a significant benefit in terms of the oxygenation index and that compared with standard oxygen therapy or a mask, the helmet does not increase PaCO 2 . As when using the common mask, employing a helmet requires the patient to have effective independent breathing, clear respiratory secretions, and haemodynamic stability.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, it was reported that MV duration is also a crucial factor influencing whether weaning can be successful [22]. Protracted MV duration is associated with respiratory muscle structural damage and muscle fiber remodeling, which leads to ventilator dependency.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data confirmed that, in a general ICU population with difficult weaning, early extubation to NIV did not shorten time to liberation from any ventilation nor improved any outcome 81 . In contrast, more recently early extubation followed by immediate NIV in hypoxaemic patients resulted in shorter length of ventilation and hospital stay, and less incidence of ventilator-associated pneumonia, without changes in mortality, compared with standard extubation 82 .…”
Section: Barcelona Respiratory Networkmentioning
confidence: 95%